Sensitivity and stability of conducting polymers and copper-based metal organic framework for optical ammonia gas sensor - Ismail, Abdul Hadi (2022)
Optical approaches for ammonia (NH3) gas sensing are contemplated as a reliable alternative to the conventional chemiresistive gas sensing techniques. Absorbance-based sensor by using white light were developed by using gasochromic materials, namely conducting polymers and copper-based metal-organic framework. Conducting polymers can be considered as the ideal material to be used as a single-component optical NH3 gas sensor at room temperature. Recent interest in metal-organic frameworks has risen significantly, owing to their high surface area and porosity, as well as the inherent convenience of sculpting to design selected coordination sites for gas adsorption. Hence, a copper-based metal-organic framework, HKUST-1, has been chosen as a potential type of MOF for the intrinsic optical NH3 gas sensor. The optical sensing performance of three different types of electropolymerised conducting polymers namely polyaniline (PANI), poly(3,4-ethylenedioxythiophene) (PEDOT) and polypyrrole (PPy), towards NH3 gas were evaluated. On the basis of the former study, bilayers and copolymers containing electropolymerised PEDOT and PANI were further probed in order to attain the desired NH3 sensing outputs from both materials. Characterisations of the samples were carried out using Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), and field emission scanning electron microscopy (FESEM) where functional group identifications of the corresponding samples and their morphological analysis were identified.. PEDOT exhibited the highest sensitivity (9.03/%) towards NH3 gas comparing to PANI and PPy with the detection limit of 2.73 ppm, which is in agreement with their respective conductivity trends. The order of the bilayers and the presence of acid dopant on the fabrication of the sensing platform produced different absorbance responses upon exposure to NH3 gas. The gasochromic behaviour of PANI and PEDOT during the adsorption of NH3 gas was closely related to the changes in the oxidation state which have simultaneously altered the colour intensity of the respective sensing layer. Meanwhile, in contrast to the in-situ works, a long-term sensitivity performance of conducting polymers and metal-organic frameworks coated on side-polished plastic optical fibre (SP-POF) was presented. Long-term sensitivity of HKUST-1, PANI in protonated (emeraldine salt, ES) and deprotonated state (emeraldine base, EB) to the high concentration of NH3 gas was performed. ES-EB composite has exhibited higher NH3 sensitivity to the sole ES and ES-(HKUST-1) with minimal loss of sensitivity. ES-EB coated SP-POF has exhibited minimal sensitivity loss to NH3 gas throughout the test duration with a 7.8% decrease followed by ES (28.1%) and ES-(HKUST-1) (50.86%). Of all developed samples in this work, PEDOT has exhibited the highest sensitivity to NH3 gas(9.03/%) while PANI (EB) has exhibited shortest response and recovery time to 1% NH3 gas, at room temperature. Also, incorporation of EB in the ES-coated SP-POF composite has significantly reduce the loss of sensitivity to NH3 gas.